MAPPING OF SACRED AREA FOR BIRD DIVERSITY IN WESTERN AREA OF MT. SEMERU - Rahmi Ipango; Luchman Hakim; Dian Siswanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Brawijaya, 2020)
Danyangan is A proof traditional conservation created by local wisdom. Knowledge of bioculture provides a facts play a role in understanding the ecological processes that occur and providing an overview local efforts in protecting the environment. The village’s. Danyangan has the form of a collection of large trees marked by the presence of sacred fig trees (Ficus sp.). Moreover, the fig tree become a habitat for several species of birds. The canopy’s cover reserves water, insects, and fruits as food for birds and creates an interesting relation as a microhabitats.The location of this study was carried out in the administrative district of Malang district in Tumpang, East Java in the area of the district located in Gubugklakah, Kunci, Drigu, Poncokusomo, Puthuk, Pandansari, Jajang, and Aran-aran. Bird observation is carried out using the point count or IPA method.The study recorded 636 individuals consisting of 31 species, 21 families and 9 orders. The birds identified were dominated by Passeriformes as many as 11 families. Based on the results, shows all locations in the danyangan area dominated by detailed Swallow (Collocalia linchii). Instead, The value of bird species abundance in all study locations is included in the high category of values ranging >4.